2019
DOI: 10.1042/bcj20190625
|View full text |Cite
|
Sign up to set email alerts
|

Resurrection of ancestral effector caspases identifies novel networks for evolution of substrate specificity

Abstract: Apoptotic caspases evolved with metazoans more than 950 million years ago (MYA), and a series of gene duplications resulted in two subfamilies consisting of initiator and effector caspases. The effector caspase genes (caspases-3, -6, and -7) were subsequently fixed into the Chordata phylum more than 650 MYA when the gene for a common ancestor (CA) duplicated, and the three effector caspases have persisted throughout mammalian evolution. All caspases prefer an aspartate residue at the P1 position of substrates,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 83 publications
2
35
0
Order By: Relevance
“…In contrast, CP162 is conserved in caspases-3 and -7 (DxxDases) as asparagine ( Figure 1 B,D and Figure 2 E). Reconstructions of ancestral effector caspases showed that the polar glutamate in the caspase-6 lineage is moved away from the S4 subsite by hydrogen bonding to a network of amino acids on helices-4 and -5, as described above [ 12 ]. The interactions result in rotation of a hydrophobic group on active site loop 4 (L4), called GP9-V01, into the S4 subsite ( Figure 1 C) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CP162 is conserved in caspases-3 and -7 (DxxDases) as asparagine ( Figure 1 B,D and Figure 2 E). Reconstructions of ancestral effector caspases showed that the polar glutamate in the caspase-6 lineage is moved away from the S4 subsite by hydrogen bonding to a network of amino acids on helices-4 and -5, as described above [ 12 ]. The interactions result in rotation of a hydrophobic group on active site loop 4 (L4), called GP9-V01, into the S4 subsite ( Figure 1 C) [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Caspase subfamilies evolved from a common ancestor that diverged into multiple caspases more than 700 million years ago [ 11 ]. We showed recently that the common ancestor of effector caspases-3, -6, and -7 was a promiscuous enzyme with little preference for aspartate or valine at the P4 site [ 12 ]. In addition, specificity for valine evolved early in the caspase-6 lineage due to introduction of a network of charged amino acids near the S4 subsite ( Figure 1 C).…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme activity was determined in a buffer of 150 mM Tris-HCl, pH 7.5, 50 mM NaCl, 10 mM DTT, 1% sucrose, 0.1% CHAPS (assay buffer) at 25 °C, as previously described (35,36).…”
Section: Enzyme Assays and Substrate-phage Displaymentioning
confidence: 99%
“…The steady-state parameters, KM and kcat, were determined from plots of initial velocity versus substrate concentration. Substrate phage display assays were performed as described (36,37). Briefly, phage libraries consisting of caspase recognition sequences were bound to Ni-NTA resin.…”
Section: Enzyme Assays and Substrate-phage Displaymentioning
confidence: 99%
“…The same study by the Wells group demonstrated that substitution of P1 glutamate by aspartate actually results in a higher rate of protein cleavage by caspases. The shared ability of caspases-3, -6, and -7 to cleave substrates after glutamate could be explained by their very similar structure, which originates from a single ancestral effector caspase gene [38]. Both P1 aspartate and glutamate appear to be conserved throughout Metazoans in general [13]; however, a taxon-oriented study showed that mammals have a lower incidence of P1 E-cut sites (3%) compared to birds (7%) and ray-finned fish (9%) (Table S3, Figure S1).…”
Section: Vertebrate Caspase Targets Are Highly Conserved At the Levelmentioning
confidence: 99%